Rekonstruksi Normatif Penegakan Hukum terhadap Kekerasan Seksual dalam Rumah Tangga Berdasarkan Undang-Undang Nomor 23 Tahun 2004 - Rufaidah Rufaidah; Iin Indriani; Sarah Alzagladi; Fitri Ramadhani (Jurnal Hukum Lex Generalis, 2026)
This study analyzes normative issues in the regulation of law enforcement regarding domestic sexual violence based on Law Number 23 of 2004. The study focuses on the discrepancy between the construction of legal norms and the need for victim protection. The method used is normative legal research with a statutory and conceptual approach. The results indicate weaknesses in the norms, particularly regarding the lack of explicit regulation of the concept of consent in marital relations and the failure to accommodate the characteristics of sexual violence in the private sphere. Furthermore, a disharmony was found with more recent developments in sexual violence regulations. Therefore, operational steps are needed in the form of reformulating the norms in Law Number 23 of 2004, developing interpretation guidelines based on victim protection, and harmonizing them with related regulations to achieve more effective and equitable law enforcement.